MULTIOBJECTIVE STOCK PORTFOLIO OPTIMIZATION USING SINE COSINE ALGORITHM WITH BUY- IN THRESHOLD AND CARDINALITY CONSTRAINTS - KABAN (NIM: 10114081), RISPANDANTA
A stock portfolio is a collection of various types of shares owned by a person or investor. In investing, return and risk are the two main bases for an investor to choose to invest or not in the stock portfolio. Therefore the arrangement of the stock portfolio must be done selectively. In this final project, the portfolio was made using a simple Markowitz model. In addition, the arrangement of portfolios with buy-in threshold and cardinality constraints will be reviewed as well. These problems will be viewed through a multi-objective perspective. To solve multi-objective problems, we use weighted sum method and epsilon constraints so that the problem becomes a single objective problem. Then the problem will be changed to a problem without constraints. Thus the problem can be solved using the sine cosine algorithm (SCA) method.